2000
DOI: 10.1897/1551-5028(2000)019<1925:eobaot>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bisphenol a on the Early Life Stage in Japanese Medaka (Oryzias Latipes)

Abstract: Abstract-Japanese medaka (Oryzias latipes) were exposed to bisphenol A (BPA) at the sublethal concentrations of 2.28, 13.0, 71.2, 355, and 1,820 g/L (as mean measured concentrations) in the early life stage from fertilized eggs to 60-d posthatch. Except for the growth and sexual differentiation of the fish at 60-d posthatch, no effects were observed on hatching success and time to hatching in embryological stage and on mortality and abnormal behavior and appearance in hatched larvae. The growth of the fish was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…There is a great deal of evidence that in vivo experimental exposure of adult male fish to BPA has detrimental effects on the gonadal morphology and histology. A few studies that can be cited with their findings are decreased spermatozoa and abnormal testicular connective tissue in Japanese medaka Oryzias latipes [15], reduced GSI and inhibition of spermatogenesis in fathead minnow Pimephales promelas [6], loss of testicular structure and increase in fibrotic tissue and decrease in number of spermatozoa in Japanese medaka Oryzias latipes [16], adverse effect on sperm quality in brown trout Salmo trutta fario [17], impaired steroidogenesis and altered gonad histology in adult common carp Cyprinus carpio [7], and impaired steroidogenesis and sperm quality, in goldfish Carassius auratus L [8].…”
Section: Discussionmentioning
confidence: 99%
“…There is a great deal of evidence that in vivo experimental exposure of adult male fish to BPA has detrimental effects on the gonadal morphology and histology. A few studies that can be cited with their findings are decreased spermatozoa and abnormal testicular connective tissue in Japanese medaka Oryzias latipes [15], reduced GSI and inhibition of spermatogenesis in fathead minnow Pimephales promelas [6], loss of testicular structure and increase in fibrotic tissue and decrease in number of spermatozoa in Japanese medaka Oryzias latipes [16], adverse effect on sperm quality in brown trout Salmo trutta fario [17], impaired steroidogenesis and altered gonad histology in adult common carp Cyprinus carpio [7], and impaired steroidogenesis and sperm quality, in goldfish Carassius auratus L [8].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] EDC activity evaluation has been conducted on various chemical compounds using fish. It has been confirmed that some chemical compounds, such as bisphenol A (BPA), [4][5][6][7][8] nonylphenol (NP) [9][10][11][12] and octylphenol (OP), 10) exhibit activity, even at relatively low concentrations. As short-term experimental methods, sex reversal and reproduction tests have been conducted by exposing parent fish to chemical compounds in water.…”
Section: Introductionmentioning
confidence: 99%
“…As experimental methods to observe long-term effects, partial life cycle and full life cycle tests have been conducted in order to clarify the effects of chemical compounds over several generations. 11,13,14) It is known that the influence of chemical exposure appears more significantly in juveniles and embryos during developmental stages than in mature parents; thus, several methods, such as exposing fry just after hatching 7,8,[15][16][17] and exposing fertilized eggs, 6,10,11,[16][17][18][19][20] as well as microinjection into fertilized eggs, 21,22) are also utilized. In a special case, artificially inseminated eggs were exposed.…”
Section: Introductionmentioning
confidence: 99%
“…This chemical has been studied mainly with regard to its effects on animal development and reproductive systems (Yokota et al, 2000;Kang et al, 2002). BPA has been described in previous reports as a very "weak" xenoestrogen because these assay systems, especially in vivo, required roughly 1,000-to 10,000-fold concentrations of BPA to exhibit estrogenic activities relative to the potency of 17β-estradiol (E 2 ).…”
Section: Introductionmentioning
confidence: 99%